Simulations and measurements in scanning electron microscopes at low electron energy. Issue 6 (10th June 2016) - Walker, Christopher G.H.; Frank, Luděk; Müllerová, Ilona
Summary: The advent of new imaging technologies in Scanning Electron Microscopy (SEM) using low energy (0–2 keV) electrons has brought about new ways to study materials at the nanoscale. It also brings new challenges in terms of understanding electron transport at these energies. In addition, reduction in energy has brought new contrast mechanisms producing images that are sometimes difficult to interpret. This is increasing the push for simulation tools, in particular for low impact energies of electrons. The use of Monte Carlo calculations to simulate the transport of electrons in materials has been undertaken by many authors for several decades. However, inaccuracies associated with the Monte Carlo technique start to grow as the energy is reduced. This is not simply associated with inaccuracies in the knowledge of the scattering cross‐sections, but is fundamental to the Monte Carlo technique itself. This is because effects due to the wave nature of the electron and the energy band structure of the target above the vacuum energy level become important and these are properties which are difficult to handle using the Monte Carlo method. In this review we briefly describe the new techniques of scanning low energy electron microscopy and then outline the problems and challenges of trying to understand and quantify the signals that are obtained. The effects of charging and spin polarised measurement are also briefly explored. SCANNING 38:802–818, 2016. © 2016 Wiley Periodicals, Inc.